2015
DOI: 10.1002/biof.1217
|View full text |Cite
|
Sign up to set email alerts
|

Regulation at multiple levels control the expression of folate transporters in liver cells in conditions of ethanol exposure and folate deficiency

Abstract: Complex regulatory mechanisms control the expression of folate transporters within cells. Liver is the primary reserve of the folate stores within the body. As excessive alcohol consumption or inefficient dietary folate intake are known to create folate deficiency, so therefore the current study was designed to explore various regulatory mechanisms controlling the expression of folate transport in liver cells in conditions of ethanol exposure and folate deficiency. In order to see whether the effects mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Several previous studies have shown that folate deficiency results in a significant upregulation of folate transport genes such as SLC19A1/RFC-1 and SLC46A1/PCFT [33, 34]. Folate deficiency also results in decreased half-lives of these two genes [35].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown that folate deficiency results in a significant upregulation of folate transport genes such as SLC19A1/RFC-1 and SLC46A1/PCFT [33, 34]. Folate deficiency also results in decreased half-lives of these two genes [35].…”
Section: Discussionmentioning
confidence: 99%
“…Folate transporters in the alcohol using/abusing pregnant woman must be downregulated at the placental level. The mechanism is perhaps similar to the downregulation of folate transporters in the context of intestinal absorption of dietary folic acid (Halsted 1980;Halsted et al 2002b;Thakur and Kaur 2015).…”
Section: Folic Acid and Alcohol (Etoh)mentioning
confidence: 98%
“…As a result, folate deficiency is a common finding in chronic alcoholics (Axelrod and Daly 1965;Eells et al 2000a;Halsted et al 2002bHalsted et al , 2010. This malabsorption has been attributed to the downregulation of folate transporters (Halsted 1980;Halsted et al 2002b;Thakur and Kaur 2015). Folate deficiency can lead to a decrease in SAM levels (Miller et al 1994).…”
Section: Folic Acid and Alcohol (Etoh)mentioning
confidence: 99%